simplify: 3x + 5y - xy when x=7 and y=3

1 answer

To simplify the expression 3x + 5y - xy when x = 7 and y = 3, we substitute the given values into the expression:

3(7) + 5(3) - (7)(3)

Simplifying further:

21 + 15 - 21

Combining like terms:

36 - 21

This results in:

15
Similar Questions
  1. simplifying square roots1) find volume of this prism? v=bwh b=√12" w=√6" h=√8" 2)simplify: √576 3)simplify: √400
    1. answers icon 3 answers
  2. Simplify 8a − 2a.Simplify 12e − 5f − 7e +3f. Simplify 9x + 3y − 6 − 5x + 4y −3. Simplify 9/11z − 4/11z. Simplify
    1. answers icon 4 answers
  3. simplifying square roots1) find volume of this prism? v=bwh b=√12" w=√6" h=√8" 2)simplify: √576 3)simplify: √400
    1. answers icon 3 answers
  4. So I need some help on these Graphing Square Root Functions Quiz questions.1. Simplify 2 over √5 2. Simplify -11√112 3.
    1. answers icon 1 answer
more similar questions